Analisa dan Perbaikan Bottleneck pada Proses Hot Press - Marcelo, Alfian; Herlina, Herlina (Fakultas Teknik UMRI, 2025)
PT. XYZ is a ceramic manufacturing company with several production lines, including the Mould Division at Plant 2, which is responsible for producing punches used as molds for the pressing machines. Based on observations and weekly production data analysis, a bottleneck was identified in the hot press process, resulting in failure to meet the production targets. This issue is indicated by a high average cycle time of 70.54 minutes per unit, which exceeds the ideal 56.25 minutes required to achieve the daily target of 8 units per shift.This study aims to identify the main causes of the bottleneck in the hot press process and propose improvements to enhance production efficiency. The methodology applied includes Value Stream Mapping (VSM) from the Lean Manufacturing framework to map the entire process flow and identify non-value-added activities. In addition, the Root Cause Analysis (RCA) method is utilized to trace the fundamental causes of the bottleneck.